2015
DOI: 10.1016/j.jom.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Are safety and operational effectiveness contradictory requirements: The roles of routines and relational coordination

Abstract: The relationship between managing a production system to be safe and managing it to be operationally effective is often described in conflicting terms, creating confusion for research and practice. Some view improving safety as separate and distinct from increasing operational effectiveness; they are contradictory requirements. Others emphasize that safety and effectiveness are complementary, and combine to enhance competitiveness. Recent research proposes that this confusion can be explained by examining the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 85 publications
(149 reference statements)
8
122
1
5
Order By: Relevance
“…Prior work has suggested that organizational complexity (Lo et al, 2014) and enhanced coordination between different management systems (Pagell et al, 2015) contribute to explain the performance of safety practices at the organizational level. In line with these studies, we explored the role of organizational and operational factors on the effectiveness of the OHSAS 18001.…”
Section: Discussion Implications and Concluding Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has suggested that organizational complexity (Lo et al, 2014) and enhanced coordination between different management systems (Pagell et al, 2015) contribute to explain the performance of safety practices at the organizational level. In line with these studies, we explored the role of organizational and operational factors on the effectiveness of the OHSAS 18001.…”
Section: Discussion Implications and Concluding Remarksmentioning
confidence: 99%
“…The prioritization of safety practices creates a safer working environment which fulfils the workers' safety needs and allows them to pursue operational goals (Pagell et al, 2015). In manufacturing businesses-characterized by a greater process automation that makes more evident the negative consequences of work accidents-the adoption of the OHSAS 18001 enhances organizational performance through the timely identification and documentation of risks and the implementation of corrective actions (Lo et al, 2014).…”
Section: Discussion Implications and Concluding Remarksmentioning
confidence: 99%
“…To collect information and validate the model in Figure 1, a designed questionnaire has been used, one of the most used methods to gather information easily and quickly [33][34][35], as well as a deep revision of literature, which allows us to identify research related to the integration and updating of IT, the implementation and the benefits of a GSC, all considered LTV. The literature revisions a rational validation of the questionnaire and identifies the items.…”
Section: Phase 1 Sample Collectionmentioning
confidence: 99%
“…Using DSR, we developed a set of interventions and mechanisms that incorporated a set of six, strong routines that fostered collaboration and coordination amongst diverse professional actors who were working towards a shared social goal of improving patient experience. Imison, Poteliakhoff, & Thompson, 2012;Pagell et al, 2015). The combined outcomes of our interventions and mechanisms include shortened waiting times in the ED, fewer cancellations of elective surgery, reduced lengths of stay, cost reductions, and increased workforce morale.…”
Section: Discussionmentioning
confidence: 99%
“…Notable in Silvester et al's (2014) work outlined in section 2.3 is the clear labeling of the practice to clearly communicate the expected outcome. Pagell et al (2015) argue that the root cause of variance in the enactment of a routine derives from a weak transmission of how a routine should be performed so that its performance aligns with its intended outcome. The importance of outcomespecificity is also captured in the work of Boyer et al (2012) as a foundation for nurturing a safety-enabling culture.…”
Section: Reducing Variation In Practice: a Routines-based Viewmentioning
confidence: 99%